Implementation of Resistance Training to Improve the Speed of Crescent Kicks in Pencak Silat Athletes - Rizky Maulana Andika; Nida'ul Hidayah; Alen Rismayadi; Mulyana (Journal of Physical Education Health and Sport, 2026)
Speed is a crucial physical component in pencak silat, particularly in executing the sickle kick technique, which plays an important role in scoring effectiveness during matches. However, school-age pencak silat athletes often demonstrate limited kick speed due to insufficient specific strength and neuromuscular development. Therefore, training methods that integrate strength development with technical movement specificity are needed to optimize performance. This study aims to analyze the effect of resistance training integrated with the sickle kick technique on increasing the speed of the sickle kick of school-age pencak silat athletes. The study used a quantitative approach with an experimental method through a one-group pretest–posttest design. The subjects consisted of 10 school-age pencak silat athletes who participated in extracurricular pencak silat activities at Muhammadiyah 6 Junior High School Bandung, with a total sampling technique. The treatment was resistance training using a resistance band which was carried out for 14 meetings with a frequency of three times per week. Measurement of the sickle kick speed was carried out by counting the number of kicks executed correctly within 10 seconds towards paching during the pretest and posttest. Data were analyzed using descriptive statistics, normality tests, and paired samples t-tests at a significance level of 0.05. The results showed an increase in the average value of the sickle kick speed from 15.60 in the pretest to 18.80 in the posttest. The paired samples t-test showed a significance value of 0.000 (p < 0.05), indicating that resistance training significantly increased the speed of the sickle kick in school-age pencak silat athletes. This finding confirms that resistance training based on specific movement techniques is effective in developing the performance of school-age pencak silat athletes.